REFORMASI PENGELOLAAN SDM APARATUR, PRASYARAT TATA KELOLA BIROKRASI YANG BAIK - Edy Topo Ashari (Pusjar SKPP Lembaga Administrasi Negara, 2010)
The success of the bureaucratic reform could be achieved if the basic foundation, namely human resource of apparatuses have been able to managed with optimal and sustainable. In order for apparatus management reforms can be realized, can be used 2 (two) approaches; using external approach, encompassing policy approaches and systems; and internal approach, encompassing approach to cultural development and the inculcation values of organization. These approaches need to be understood and become a main point in setting the policy direction of apparatus management that is more productive, efficient, and effective. Keywords : Bureaucratic Reform, Apparatus Management